Which are determinants of firm innovation in Vietnam? A micro analysis - Le, Thi Ngoc Bich (University of Economics Ho Chi Minh City, 2023)
This study sets out to investigate the factors influencing Vietnam firms’ innovation in various sectors by using World Bank (2015) enterprise survey of 996 firms across the country. We employ ordinary least squares (OLS), probit model, and marginal effect to estimate the impact of firm characteristics, industry characteristics, and business climate on different facets of innovation, including technology and non- technology. Quantitatively, we find that direct exporters, firm size, state ownership, email using, and competition increase the probability of technology innovation. Meanwhile, foreign ownership impacts negatively on innovation in all aspects, technology and non-technology innovation. Firm age and bribery are not influential factors to innovation in all cases. From the findings of analysis, a few policy implications regarding the studied factors are drawn for better environment for firm innovation.